Detection of l-alanylaminopeptidase activity in microorganisms using fluorogenic self-immolative enzyme substrates. Issue 18 (15th September 2016) - Cellier, Marie; James, Arthur L.; Lowe, Jonathan; Orenga, Sylvain; Perry, John D.; Rasul, Ari K.; Stanforth, Stephen P.
Graphical abstract: Abstract: A series of fluorogenic enzymatic substrates that incorporate a self-immolative spacer were synthesised for the purpose of identifyingl -alanylaminopeptidase activity in microorganisms in agar media. These substrates resulted in the generation of fluorescent microorganism colonies with Gram-negative microorganisms.